2006
DOI: 10.1074/jbc.m512866200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Kv3.1b Potassium Channel Phosphorylation in Auditory Neurons by Conventional and Novel Protein Kinase C Isozymes

Abstract: In fast-spiking neurons such as those in the medial nucleus of the trapezoid body (MNTB) in the auditory brainstem, Kv3.1 potassium channels are required for high frequency firing. The Kv3.1b splice variant of this channel predominates in the mature nervous system and is a substrate for phosphorylation by protein kinase C (PKC) at Ser-503. In resting neurons, basal phosphorylation at this site decreases Kv3.1 current, reducing neuronal ability to follow high frequency stimulation. We used a phospho-specific an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…One way PLC may influence K V currents is via protein kinase C (PKC) because PLC is known to modulate PKC activity via degradation of phosphatidylinositol 4,5-bisphosphate into diacyl glycerol and inositol 1,4,5-trisphosphate. Previous work on K V modulation in the mammalian sound localization circuit, as well as in many other brain regions, has shown that PKC can modulate HTK currents (Atzori et al, 2000; Sun et al, 2003), including HTK currents mediated by K V 3.1 channels (Critz et al, 1993; Liu and Kaczmarek, 1998; Macica et al, 2003; Song et al, 2005; Song and Kaczmarek, 2006). To test whether PKC was involved, slices were pre-incubated for at least 30 mins in a cell permeable PKC blocker Go6983 (20 nM), which non-selectively blocks all PKC subunits with the exception of PKC μ (Gschwendt et al, 1996; Peterman et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One way PLC may influence K V currents is via protein kinase C (PKC) because PLC is known to modulate PKC activity via degradation of phosphatidylinositol 4,5-bisphosphate into diacyl glycerol and inositol 1,4,5-trisphosphate. Previous work on K V modulation in the mammalian sound localization circuit, as well as in many other brain regions, has shown that PKC can modulate HTK currents (Atzori et al, 2000; Sun et al, 2003), including HTK currents mediated by K V 3.1 channels (Critz et al, 1993; Liu and Kaczmarek, 1998; Macica et al, 2003; Song et al, 2005; Song and Kaczmarek, 2006). To test whether PKC was involved, slices were pre-incubated for at least 30 mins in a cell permeable PKC blocker Go6983 (20 nM), which non-selectively blocks all PKC subunits with the exception of PKC μ (Gschwendt et al, 1996; Peterman et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Augustine and Bezanilla, 1990; Atzori et al, 2000; Strumbos et al, 2010). Much of the literature concerning phosphorylation-induced changes in K V 3 currents has shown that PKC is intimately involved (Liu and Kaczmarek, 1998; Macica et al, 2003; Sun et al, 2003; Song et al, 2005; Song and Kaczmarek, 2006). However, exactly how activation of mGluR II leads to activation of the G βγ complex, which changes PKC activity via PLC, and ultimately causes an enhancement of HTK currents in NL neurons, awaits more investigation.…”
Section: Discussionmentioning
confidence: 99%
“…1C). Besides mediating such retro-suppression of neurotransmission, activation of group I mGluRs also increases phosphorylation of K v 3.1b (Song and Kaczmarek, 2006), which is a critical factor defining the ability of MNTB neurons to follow high frequency inputs (reviewed in Johnston et al, 2010). Physiological function of group II mGluRs in MNTB is not known.…”
Section: Anatomy and Physiology Of Mglurs In Mammalian Mntbmentioning
confidence: 99%
“…To this end, we compared the gene expression profile of the rat SOC in P16 males and females. This juvenile age is often used in functional SOC studies, as most properties resemble the mature situation (Ehrlich et al, 1999;Srinivasan et al, 2004;Klug and Trussell, 2006;Song and Kaczmarek, 2006;Smith et al, 2000). To validate our approach, we also analyzed the adult pituitary gland, which plays a central role in sexual development and displays anatomical (MacMaster et al, 2007) and transcriptional (Nishida et al, 2005;Zhan and Desiderio, 2003) sexual dimorphisms.…”
Section: Introductionmentioning
confidence: 98%